(untitled) (Bangladesh Journal of Medicine, 2026)
Subclavian artery thrombosis is a rare but clinically significant condition that can present with upper limb ischemia and neurological symptoms. While atherosclerosis remains the most common cause, hypercoagulable states such as hyperhomocysteinemia are increasingly being recognized as potential contributors.We report the case of a 40-year-old chronic smoker who presented with progressive pain, numbness, and weakness in the left upper limb. Clinical examination revealed absent pulses and a significant blood pressure discrepancy between the arms. CT angiography demonstrated thrombotic occlusion in the proximal segment of the left subclavian artery. Laboratory workup showed a markedly elevated serum homocysteine level (43 μmol/L), reduced protein C (65%) and protein S (51%) levels, and a positive Factor V Leiden test. Antithrombin III was within normal range (111%). Interestingly, fasting serum vitamin B12 and folate levels were elevated (980 pg/mL and 120 ng/mL, respectively). The patient was managed with anticoagulation, antiplatelets, and vitamin supplementation, and showed clinical improvement.This case underscores the importance of evaluating metabolic and thrombophilic risk factors, including hyperhomocysteinemia and inherited thrombophilia, in patients with arterial thrombosis at uncommon sites or in the absence of conventional risk factors. Early identification and correction can guide targeted therapy and potentially prevent recurrence. Bangladesh J Medicine 2026; 37(1): 62-67